Incident Vertebral Fractures and Risk Factors in the First Three Years Following Glucocorticoid Initiation Among Pediatric Patients With Rheumatic Disorders. (26th May 2015) - LeBlanc, Claire MA; Ma, Jinhui; Taljaard, Monica; Roth, Johannes; Scuccimarri, Rosie; Miettunen, Paivi; Lang, Bianca; Huber, Adam M; Houghton, Kristin; Jaremko, Jacob L; Ho, Josephine; Shenouda, Nazih; et al.
ABSTRACT: Vertebral fractures are an important yet underrecognized manifestation of osteoporosis in children with chronic, glucocorticoid‐treated illnesses. Our goal was to determine the incidence and clinical predictors of vertebral fractures in the 3 years following glucocorticoid initiation among pediatric patients with rheumatic disorders. Incident vertebral fractures were evaluated according to the Genant semiquantitative method on lateral radiographs at baseline and then annually in the 3 years following glucocorticoid initiation. Extended Cox models were used to assess the association between vertebral fractures and clinical risk predictors. A total of 134 children with rheumatic disorders were enrolled in the study (mean ± standard deviation (SD) age 9.9 ± 4.4 years; 65% girls). The unadjusted vertebral fracture incidence rate was 4.4 per 100 person‐years, with a 3‐year incidence proportion of 12.4%. The highest annual incidence occurred in the first year (6.0%; 95% confidence interval (CI) 2.9% to 11.7%). Almost one‐half of the patients with fractures were asymptomatic. Every 0.5 mg/kg increase in average daily glucocorticoid (prednisone equivalents) dose was associated with a twofold increased fracture risk (hazard ratio (HR) 2.0; 95% CI 1.1 to 3.5). Other predictors of increased vertebral fracture risk included: (1) increases in disease severity scores between baseline and 12 months; (2) increases in body mass index Z ‐scores in the first 6 months of each 12‐month period preceding the annual fracture assessment; and (3) decreases in lumbar spine bone mineral density Z ‐scores in the first 6 months of glucocorticoid therapy. As such, we observed that a clinically significant number of children with rheumatic disorders developed incident vertebral fractures in the 3 years following glucocorticoid initiation. Almost one‐half of the children were asymptomatic and thereby would have been undiagnosed in the absence of radiographic monitoring. In addition, discrete clinical predictors of incident vertebral fractures were evident early in the course of glucocorticoid therapy. © 2015 American Society for Bone and Mineral Research.